Development of Cultural Tourism in Macau through the Visual and Performing Arts - Tique, Ana Teresa Leal (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The effect of managers' cultural and educational background on management style: a study of middle level managers in Macao - Tam, Hoi Iong (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Towards an architecture center in Macau: vision and feasibility - Simões, Ana Filipa Brito da Cruz Rodrigues (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring the role of vocational education in promoting the diversification of Macao's industry: a study of the cultural and creative industries - Ngai, Hio Peng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Employee Motivation in Social Enterprise: The Case of Caritas Elderly Care Services in Macau - Mui, Un Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Corporate Social Resopnsibility Practices in Macau - Marcelo, Nicole Chantal Clemente (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Financial Valuation of Walmart Inc - Lestro, Gonçalo Nuno das Neves Arrojado (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Consumer purchase intention towards floral products: a study based on the five consumption values - Lei, Si Nga (University of Saint Joseph, 2023)
This dissertation focused on the consumers’ consumption behavior in Macau flower retailers. It revealed what factors affect consumers’ choice of flower shops during purchase. Also, what contributes to the customers’ loyalty towards a flower retailer by having interviews with the female target groups aged between 20 to 50 who work in the office. This study is important to the flower business owner because the result can allow them to understand the thoughts and feelings of their consumer. By interviewing 11 heavy users of floral products with 16 questions based on the five consumption values, we can communicate with the consumers directly and learn the reasons behind their purchasing behavior. Questions have been divided into 5 consumption values according to the previous research by (Sheth, Newman, & Gros, 1991), including functional, conditional, social, emotional, and epistemic values. The research has collected data on how and at what level these values may affect consumer consumption choices individually. The finding part analyzed the reason why those values affect consumers’ choices. Most of the interviewees stated that service is the most important compared to quality because the owner should be enthusiastic to provide product information and understand the consumer very well to impress and retain them with good personal service
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; consumption behavior; floral product; purchase intention

Enhancing Learning of Accounting for Non-Accounting students: Through Lens of Theory of Planned Behavior and Experiential Learning Styles - Lau, Meng Chan (University of Saint Joseph, 2020)
This thesis aims to explore how learning accounting for non-accounting major students could be enhanced through a comprehensive framework connecting individual attributes and learning approaches. While accounting is considered an important and mandatory discipline for business students, it is also considered a difficult subject which deters students’ engagement in the subject. Although the issue has been widely recognized, there are relatively less discussions on possible remedies. Learning accounting is a dynamic process that go beyond the traditional one-to-many learning and teaching settings, all factors revolving the students’ learning environment and process, altogether determine and affect the learning efficiencies. A meta-analysis was first performed to understand the standings of accounting education and to identify gaps within existing literatures in the field of management, accounting, tourism and general education researches. A documentary review on the curricula of all Macau HEI programs involving compulsory accounting courses was also conducted to understand the role and significance of accounting courses for non-accounting college students in Macau. Based on the literature review, this study borrows constructs from theory of planned behavior (TPB) models in its research framework. It attempts to provide a comprehensive framework to understand how students learn accounting efficiently by delving into individual learning styles of the students and their perceived helpfulness and self-efficacy, in respective to different learning techniques. Due to its exploratory nature, a mixed method of qualitative and quantitative methodology is adopted, where both focus group discussions and in-depth interviews are performed with non-accounting students to elicit understandings on student’s difficulties in learning accounting and their preferences for different learning styles. Then, a full-scale quantitative survey is conducted in a Macau higher education institute to assess the learning efficiencies of accounting in different situations. A triangulation with feedback from faculties and administrators are also elicited to provide alternate dimensions on the issues. With no surprise, there is no one best 3 teaching style or method for all students, this thesis contributes to accounting education research by provide a comprehensive diagnosis on the all-round learning stimulus and hindrance in learning accounting. At the end, recommendations are provided for accounting educators to emphasize on the uniqueness of students and to encourage a more dynamic and open environment for learning. Limitations of the studies are also discussed
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Adapting the Unified Theory of Acceptance and Use of Technology 2 (Utaut 2) to Explain Acceptance of Battery Electric Vehicles: Evidence From Macau - Lampo, Alessandro (University of Saint Joseph, 2020)
Vehicles solely powered by electricity are a major technological innovation that combines individual transportation needs and environmental sustainability, yet their market penetration is low. Research has traditionally indicated factors such as the vehicle’s purchasing price, driving range, and charging time as the main barriers to adoption. However, the decision to adopt a technology also depends on what the technology represents to the user; therefore, other factors may be important to explain individuals’ behavior. This study is a quantitative and cross-sectional look at the behavioral intention to adopt battery electric vehicles (BEVs) technology in the context of Macau. The research builds on the unified theory of acceptance and use of technology 2 (UTAUT 2) (Venkatesh et. al., 2012) to explain the characteristics of the local consumers. Besides the addition of image and environmental concern to the theoretical model, the study also put forward and evaluate the construct of technology show-off, an original measure of the visible and experiential characteristics of a technology. A sample of 236 Macau residents was analyzed by structural equation modeling (SEM). The analysis of the data supported the explanatory and predictive power of our model and helped to describe the idiosyncrasies of local residents. The results provide insights related to individual technology acceptance that could be useful in designing more accurate strategies and fostering the uptake of BEVs in Macau or markets that share similarities
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; Thesis and Dissertations PhD in Business Administration (D-BA); University of Saint Joseph

A Conceptual Model of Behavioral Factors Affecting the Adoption of E-government Services in Macao SAR - Iong, Kit Yeng (University of Saint Joseph, 2022)
Information and communication technologies (ICTs) are highly associated with the study of e-government, and many scholars believe that within the coming decades, government operation and policy decision-making cannot persist without the use of ICTs (Van Dijk, 2018). This thesis aims to generate a conceptual framework of the behavioral factors that could contribute to the acceleration of the implementation of e-government services in Macao SAR. Rather than regarding e-government services as a goal to be realized in traditional practice through evaluating the outcome, a process-oriented study was conducted. The e-government services are regarded as advanced tools in the 21st century to transform Macao into a smart city. The design of the process-oriented approach and the comparative study of four groups of Macao citizens' behavioral intentions are solidly supported by the research gaps identified in the literature review of e-government studies in an international perspective and the actual context of local Macao studies. Under the framework of the Theory of Planned Behavior (Ajzen, 1985, 1991), the behavioral factors of the general public and civil servants are investigated through a qualitative approach, and the findings are triangulated from various aspects. Firstly, a systematic literature review of TPB was conducted thoroughly to better understand the current study of e-government around the world. Secondly, a content and thematic analysis of the official documents and articles from local press media and research institutes related to the topic of e-government services was carried out to demonstrate a more comprehensive picture of the current problems of implementing iv and adopting e-services in Macao SAR. Observations in some government premises that provided e-services and 40 in-depth interviews were conducted to generate detailed and first-hand data. Key issues were extracted from the interviewees’ narratives and daily actual usages. Different conceptual models for different age groups and civil servant group were formed. Special attention was paid to analyzing the "hard-to-reach" groups' behavioral intentions. Research limitations identified from the previous literature were overcome partially in this study too. After comparing the similarities and differences, a new conceptual model of significant behavioral factors that affect the behavioral intentions in adopting e-government services was built. Results and findings from the analysis could be used to develop effective interventions by the government policymakers in responding to the behavioral change of the general public in the aspect of e-government services acceptance and adoption
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

A Study of Social Enterprises in Macau: The Contributing Factors to The Development of Hybrid Social Enterprises - Hau, Pak Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Comparative study: The Human rights situation in China, the USA and Europe - Chu, Pok Tou; Lao-Phillips, Jenny Oliveros (University of Saint Joseph, 2023)
This thesis mainly discusses and compares the human rights situation and the problems in China, the USA and the UK. Also, the thesis will give the solution of how to make the world's human rights situation more fairly. Because we sometimes listen to these countries use cruel ways to suppress the opponents from the news. So I think this will be very suitable for understanding the current human rights situation, problems and movements in these countries. This thesis mainly uses the secondary data analysis method to collect and analyse the data. After analysing the data, three main issues affecting human rights were identified. These issues are race, religion, and network privacy. Other important factors still influence human rights, but this dissertation focused on the three issues identified. Finally, I will give two to three recommendations to practice human rights more fairly. Although the step will be very small, we can greatly improve the fair human rights in the future
Keywords: China; Europe; Human rights; Human rights situation; Thesis and Dissertations Master of Government Studies (MGS); USA; United Kingdom; University of Saint Joseph

How Does Employer Brand Affect Employer of Choice? A Case Study of Two Macau F&B Groups’ Employer Branding Comparisons - Chen, Zhi Yi (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The attractiveness of Taobao: why do people always come back despite negative feedback - Chan, Nga Man (University of Saint Joseph, 2023)
Online shopping in Macau has developed rapidly in recent years. And the success of Taobao is significantly hard to not notice. Its’ sales are breaking the record every year. However, there are a lot of negative comments towards Taobao. Various researches and data have shown that live-streaming is one of the biggest contributions towards Taobao’s sales and record breaking. This research aims to investigate deeply to understand how Taobao counters those issues and the role of live-streaming in relation to it. Based on a review of the literature in the relevant areas , qualitative methodology is adopted after thorough considerations. A small sample size of 10 were selected to conduct semi-structured in-depth interviews and the participants agreed to respond to answer the original interview questions and the follow-up questions. Analysis of the responses demonstrated e-customer service is the most influential variable towards repurchase intention. Live-streaming strategy can effectively and directly reduce constomer’s uncertainty of products and increase the efficiency of responsiveness. And product uncertainty and responsiveness speed are variables that impact purchase intention. The result demonstrated live-streaming's effectiveness in combating multiple negative aspects of Taobao and strengthening the positive aspects. On this basis, live-streaming is an impactful method to combat Taobao. In addition, e-service in terms of sufficiency of the staff’s communication skill have been found important towards customer’s satisfaction. A gap related to such an issue has been recommended in the further research recommendations along with other factors or sample groups, which are needed to explore deeply in the future
Keywords: Authenticity; Customer satisfaction; E- Service quality; Repurchase intention; Taobao; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Till Death Do (Not) Us Part: Elderlies’ Preparation on Wealth Transmission and the Effectiveness of Testaments in Macao - Chan, Hong Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Factors Influencing Disability Inclusion Practice in Social Media: A Case Study of MDA Service Centre for the Deaf - Chan Wai Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Study of management style in Canada - Ao, Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The 50 Reasons for Voluntary Turnover: A Qualitative Exploration of Factors Contributing to Former Teacher Attrition in Macau - Ao, I. Leng (University of Saint Joseph, 2023)
Teacher turnover is a global issue that has not received much research attention in Macau despite studies indicating that teachers in the region experience high levels of stress and burnout. Given that private school teachers account for a significant proportion (88.6%) of the non-tertiary education system in Macau, this qualitative study focused on this specific group who voluntarily resigned from their positions. Through in-depth interviews with 13 former teachers from different kindergartens, primary, and secondary schools, the research identified 50 reasons categorized into 15 factors under three categories. Although schoolrelated factors account for the most, personal reasons were found to be the primary driver. The findings of the study highlight the complex nature of teacher turnover which can be attributed to both single and multiple factors, in both direct and indirect forms. The factors could also interplay in both unidirectional and mutual relationships. A conceptual framework for teacher turnover in Macau was developed to address the 15 contributing factors and the complex interplay of these factors. This study could fill the gap in the literature and serve as a valuable resource for policymakers and school leaders seeking to reduce teacher attrition rates in the region
Keywords: Macau; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; leavers; teacher turnover